Taj Mahal - Tillotson, Giles, Giles (Harvard University Press, 2022)
The meaning of the Taj Mahal, the perceptions and responses it prompts, ideas about the building and the history that shape them: these form the subject of Tillotson's book. More than a richly illustrated history, this book is an eloquent meditation on the place of the Taj Mahal in the cultural imagination of India and the wider world